Keadilan Prosedural dan Kepastian Hukum dalam Perkara Perdata (Analisis Yuridis Putusan Mahkamah Agung Nomor 555 PK/Pdt/2023) - Reynold Simandjuntak; Claudio Junior Willem Rambing (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
Judicial review (PK) in the Indonesian legal system often presents a tug-of-war between the principles of procedural justice and legal certainty, particularly following the expansion of the scope of judicial review through various regulations and court procedures. This article specifically examines Supreme Court (MA) Decision Number 555 PK/Pdt/2023 as a case study to assess the extent to which the Supreme Court is able to balance these two principles in civil court practice. Using a juridical-normative approach and analyzing empirical data, this article finds that while judicial review functions as a corrector of judicial errors to achieve substantive justice, its application must still be strictly limited by clear formal and material standards to maintain stability and legal certainty in the judicial system. This study recommends strengthening guidelines for evaluating new evidence and reforming judicial review mechanisms that are more adaptive to modern legal developments, so that justice and legal certainty can coexist in Indonesian judicial practice.